Sempre più in alto. Affrontare le sfide lanciate dal settore delle costruzioni verticali (GEOmedia, 2020)
Population growth exerts ever greater pressure on the world of construction, both in terms of buildings and infrastructure, globally. The numbers continue to increase and more and more people decide to moveto cities, so much so that by 2050 70% of the world population is expected to live in urban areas. There is little space available and there are many accommodations to be found, so construction companies are working to find a solution.As you know, however, this sector is struggling to keep up with modernization, but creating vertical projects with traditional workflows is proving to be a slow and difficult process. Professionals, as well as government bodies, are urging project teams to adopt new digitalmethods to avoid taking on the additional costs and wasted time associated with any rework.Chris Emery, already Topcon Positioning's Senior Vertical Construction Manager, talks to us about modern technologies that allow you to increase productivity and reduce conflicts and errors in projects that "pointupwards", speeding up delivery times, increasing profits and at the same time acquiring real digital twins.